Business Model and Character of Successful Millennial Agripreneurs During The Covid-19 Pandemic - Mahbubi, Akhmad (School of Business, IPB University (SB-IPB), 2022)
In 2020, the Ministry of Agriculture released at least 100 millennial agriprineurs successfully overcoming the harmful effects of Covid-19. Successful-millennial agripreneurs during the Covid-19 pandemic can be an inspiration for all agricultural stakeholders. Therefore, the business model and character of millennial agripreneurs who successfully deal with the covid-19 outbreak must be explored, studied, and duplicated. This study aims to describe a successful business model developed by millennial agripreneurs during the covid-19 pandemic and the character of successful millennial agripreneurs in the era of the covid-19 pandemic. This study uses a descriptive research design with qualitative research methods. The subjects of this study were 163 successful millennial agripreneurs during the covid-19 pandemic. They were interviewed and published by online media from 2020 to 2021. One of them, the owner of Eptilu farm, was directly interviewed in September 2021. The reliable qualitative analysis showed that the kappa coefficients were 0.90 and 0.86 (> 0.75 is excellent agreement). The business models of successful millennial agripreneurs during the covid-19 pandemic are generally online-based, categorized as brick-and-click, marketplaces, and peer-to-peer fintech. Based on the business activity model, successful millennial agripreneurs focus on farming or animal husbandry activities and post-harvest or processed agricultural products on commodities, vegetables, and livestock. Furthermore, there are dominant characteristics possessed by successful millennial agripreneurs during the covid-19 pandemic: innovative, critical thinking, visionary, cooperative, enthusiastic, and willingness to learn and share. Keywords: business activity model, business structure model, character, entrepreneurship, soft skills